Energy Systems and Management - Bilge, Ali Nezihi (Springer, 2015)
Readers of this work will find examinations of the current status and future status for energy sources and technologies, their environmental interactions and the relevant global energy policies. The work begins with an overview of Energy Technologies for a Sustainable Future, which examines the correlation between population, economy and energy consumption in the past, and reviews the conventional and renewable energy sources as well as the management of them to sustain the ever-growing energy demand in the future. The rest of the chapters are divided into 3 parts; the first part of the book, “Energy Sources, Technologies and Environment”, consists of 12 chapters, which include research on new energy technologies and evaluation of their environmental effects. The second part “Advanced Energy Materials” includes 7 chapters devoted to research on material science for new energy technologies. The final section titled “Energy Management, Economics and Policy” is comprised of 10 chapters about planning, controlling and monitoring energy related processes together with the policies to satisfy the needs of increasing population and growing economy. The chapters are selected works from the International Conference on Energy and Management, which was organized by Istanbul Bilgi University Department of Energy Systems Engineering and PALMET Energy to share the knowledge on the recent trends, scientific developments, innovations and management methods in energy, and held on 5–7th June 2014 at Istanbul Bilgi University.